2010
DOI: 10.1002/elan.201000132
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Reduction of Peroxy Disulfate on the Palladized Aluminum Electrode Modified by Prussian Blue: Application to the Analysis of Decolorizing Powders

Abstract: The mechanism of catalytic reduction of peroxydisulfate on the palladized aluminum electrode modified by Prussian blue (PB/Pd-Al) was studied. The charge transfer-rate limiting step as well as overall reduction reaction of S 2 O 8 2À is found to be a one-electron and two-electron abstraction respectively. The modified electrode is exploited for the hydrodynamic amperometry of peroxydisulfate. It is found that the calibration graph is linear in the S 2 O 8 2À concentration range 5 10 À6 -1.5 10 À3 mol L À1. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In addition, a comparison of the proposed method with other electrochemical methods is listed in Table 1 [12,[44][45][46]. Comparison with the analytical characteristics of the previous reports for COD determinations showed that the prepared modified electrode in the present work has a much lower detection limit with a wide linear dynamic range.…”
Section: Analytical Performance Characteristicsmentioning
confidence: 86%
See 2 more Smart Citations
“…In addition, a comparison of the proposed method with other electrochemical methods is listed in Table 1 [12,[44][45][46]. Comparison with the analytical characteristics of the previous reports for COD determinations showed that the prepared modified electrode in the present work has a much lower detection limit with a wide linear dynamic range.…”
Section: Analytical Performance Characteristicsmentioning
confidence: 86%
“…Some electrochemical methods have been reported in the literature for determination of 3-methylmorphine [11,12]. Ganjali et al described a new electrochemical method with an Au microelectrode as working electrode, based on FIA and fast Fourier transforms cyclic voltammetry (FFTCV) for the determination of COD alone in human plasma sample [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, electroanalytical methods have advantages such as high sensitivity, inexpensive equipment, low costs, and relative simplicity. Some electrochemical methods have been reported in the literature for determination of 3‐methylmorphine 11, 12. Ganjali et al.…”
Section: Introductionmentioning
confidence: 99%
“…Pournaghi‐Azar and Saadatirad have described determination of COD using the aluminum electrode modified by palladium with detection limit of 5 µmol L −1 . This electrode is usable in electroanalysis of COD in synthetic tablet samples 12. Acetaminophen (paracetamol, N ‐acetyl‐ p ‐aminophenol, AC) (Figure 1b) is an extensively used antipyretic analgesic drug and a suitable alternative for patients who are sensitive to aspirin 13.…”
Section: Introductionmentioning
confidence: 99%